2013
DOI: 10.1002/jgra.50143
|View full text |Cite
|
Sign up to set email alerts
|

How simulated fluence of photons from terrestrial gamma ray flashes at aircraft and balloon altitudes depends on initial parameters

Abstract: [1] Up to a few years ago, terrestrial gamma ray flashes (TGFs) were only observed by spaceborne instruments. The aircraft campaign ADELE was able to observe one TGF, and more attempts on aircraft observations are planned. There is also a planned campaign with stratospheric balloons, COBRAT. In this context an important question that arises is what count rates we can expect and how these estimates are affected by the initial properties of the TGFs. Based on simulations of photon propagation in air we find the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
2
8
1
Order By: Relevance
“…If instead, we used 10 keV, we would expect approximately 4 × 10 17 gamma rays, in approximate agreement with the Xu et al result. In summary, our work is in very good agreement with results from Geant3 and SWORD/Geant4 and in approximate agreement with the Xu et al [2012] results, although not enough information was provided in that paper to do a precise comparison. On the other hand, our results disagree with the Carlson et al [2007], the Hansen et al [2013], and the Gjesteland et al [2015] work, being an order of magnitude larger than the first and about an order of magnitude smaller than the latter two. Such differences will have a significant impact on the predicted currents and optical emissions and so need to be addressed.…”
Section: Discussioncontrasting
confidence: 99%
“…If instead, we used 10 keV, we would expect approximately 4 × 10 17 gamma rays, in approximate agreement with the Xu et al result. In summary, our work is in very good agreement with results from Geant3 and SWORD/Geant4 and in approximate agreement with the Xu et al [2012] results, although not enough information was provided in that paper to do a precise comparison. On the other hand, our results disagree with the Carlson et al [2007], the Hansen et al [2013], and the Gjesteland et al [2015] work, being an order of magnitude larger than the first and about an order of magnitude smaller than the latter two. Such differences will have a significant impact on the predicted currents and optical emissions and so need to be addressed.…”
Section: Discussioncontrasting
confidence: 99%
“…With an angular distribution of around 40°, we have adjusted for the angular dependence by using C for α < 40 and 2* C for α > 40. To get the numbers of 10 17 and 10 18 as given in literature [ Hansen et al , 2013; Dwyer et al , 2012], the value is of the order of 10 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Both Østgaard et al [] and Hansen et al [] suggest that all lightning could produce TGFs if they are faint enough not to be observed from space, and of course that is possible; and as far as space observations are concerned, it must also be possible that even bright TGFs could be associated with all lightning if most of them are hidden from observation from space by being either very low in the atmosphere or beamed downward instead of upward. As we discuss limits on the number of lightning flashes that can producing TGFs based on what is seen from orbit, we will have to consider two possibilities: that there is a very large population of very faint TGFs and that there is a population of brighter TGFs (whether or not they are as bright as those seen from orbit) buried deep in the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Østgaard et al [2012] combined ADELE's detection rate (1/1213 flashes within 10 km and 0/133 flashes within 4 km) with a cutoff power law distribution derived from spacecraft data (see below) to suggest that approximately 2% of lightning produces a TGF somewhere in the distribution, noting also that a distribution that flattens out at low luminosity could give a TGF yield of up to 100% of lightning with TGFs occurring down to about 10 12 relativistic electrons. Hansen et al [2013] performed a second set of simulations that gave a different estimate for ADELE's sensitivity, suggesting that those limits should be weaker by about an order of magnitude, but even under that assumption they represent significant limits on TGF production at low altitude that could not be obtained from space. The distribution of TGF intensities observed from space was suggested by Collier et al [2011] to be qualitatively consistent with a power law, based on both the observed intensity distribution and the decrease of maximum observed intensity with the distance along Earth's surface between the subsatellite point on the Earth and the TGF source position.…”
Section: Introductionmentioning
confidence: 99%